Learning Assistance For Blind Students to Improve Mathematical Ability - Dian Permatasari (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2022)
In Indonesia, an education system is implemented where students with special learning needs can get an education in public schools. One type of child with special needs accepted by public schools is blind. Blind children usually have various things during learning, such as difficulty in understanding abstract concepts, low learning motivation, slow to understand the material, and need to understand repetitive material. Therefore, community service is required to provide special assistance to blind students to help students learn mathematics. Partners in this service are two blind students from MAN 2 Sleman. The stages of this service consist of 3 stages, namely the preparation, assistance and evaluation stages of learning. The results of the community service show that there is an increase in mathematical understanding for blind students. In addition, students become easier to understand